Different treatment strategies for acromioclavicular dislocation injuries: a nationwide survey on open/minimally invasive and arthroscopic concepts - F. Allemann; S. Halvachizadeh; M. Waldburger; F. Schaefer; C. Pothmann; H. C. Pape; T. Rauer (European Journal of Medical Research, 2019)
Abstract Background Injuries to the acromioclavicular (AC) joint are one of the most common among sporting injuries of the upper extremity. Several studies investigated different treatment options comparing surgical and non-surgical treatment, and type of operative interventions. This study aims to evaluate treatment decisions regarding injuries of the AC joint and to compare different treatment strategies depending on the specific training of the treating physician. Methods We performed a nationwide survey by contacting different experienced physicians and sending them questionnaires. The questionnaire included 37 questions that assessed preferred treatment strategies in AC joint injuries. We addressed different surgical and nonsurgical options as well as level of experience and factors that might influence the decision on treatment strategy. The physicians were stratified according to their training into general surgeons (group trauma associated) and orthopedic surgeons (orthopedic associated). The AC joint lesions were categorized according to the widely used Rockwood classification. Results This study analyses 96 questionnaires. We included 46 (47.9%) colleagues in group trauma and 50 (52.1%) in group orthopedics. Most of the colleagues (98.9%) prefer non-operative treatment of type I and type II AC lesions. Similarly, 96.8% agree on surgical treatment of types IV, V, and VI lesions. The treatment of type III lesions is performed in 41.6% of cases non-operatively and in 58.4% of cases surgically. Trauma-associated colleagues are 3.4 times more likely to treat AC lesions with a hook plate compared to orthopedic-associated colleagues (p = 0.05). In decreasing order, the most commonly used non-surgical technique is sling immobilization (63.7%), and the most commonly performed surgical treatment is the hook plate (41.1%) in treating type III injuries. Conclusion This study shows a distinct difference in treatment of AC joint injuries depending on the training of the physician. Further, the need for high-quality studies arises to define the optimal treatment of type III lesions.